Peningkatan Kesadaran Masyarakat Pesisir Desa Hanura Terhadap Risiko Penyakit Malaria Melalui Pendekatan Partisipatif - Endah Setyaningrum; Nuning Nurcahyani; M. Kanedi; Salman Farisi; Jeany Audina Suryaningkunti; Lisa Vegita; Febrian Cahyadi; Ainun Rizqi Indriani (AMMA : Jurnal Pengabdian Masyarakat, 2026)
The population of Indonesia is around 32%  still lives in districts/cities at risk of contracting malaria. In addition, there are 154 districts/cities that fall into the low endemic area strata, 31 moderate endemic areas and 23 highly endemic areas. Hanura Village, Pesawaran Regency is one of the villages in Lampung Province that is still classified as a malaria endemic area. Hanura Village is one of the coastal areas in Lampung Province that has a high potential for the spread of malaria. Humid environmental conditions, the presence of standing water, and lack of public awareness regarding prevention efforts make this area vulnerable to an increase in malaria cases. This community service aims to increase the understanding and awareness of the Hanura Village community about the risks of malaria and its prevention measures through a participatory approach that actively involves the community. Based on these problems, it is necessary to increase awareness of the coastal community in Hanura Village about the risks of malaria through a participatory approach. The activity is carried out in several stages, namely identifying problems with the community, socialization and discussions regarding malaria and its causative vectors, education on malaria control, the use of mosquito repellent plants, and healthy and clean living behaviors. Through participatory methods, the community becomes the main actor in designing and implementing solutions relevant to their local conditions. This activity was attended by 20 villagers consisting of hamlet heads, integrated health post (Posyandu) cadres, PKK cadres, and village staff. Based on the evaluation results of the written test at the beginning of the activity (pre-test) and the written test at the end of the activity (post-test) of this training, showed an increase in knowledge of 37.8%. This activity was deemed successful because it was able to increase the understanding and awareness of the coastal community regarding the risk of malaria. The participants who attended were very enthusiastic about participating in the series of trainings and provided positive responses that are expected to support efforts to reduce malaria cases in Hanura Village.